Production of Biogasoline via Pyrolysis of Oleic Acid Basic Soaps - Endar Puspawiningtiyas; Tirto Prakoso; Meiti Pratiwi; Subagjo Subagjo; Tatang Hernas Soerawidjaja (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
In this study, an investigation on the effect of the Ca/Mg/Zn mixing ratio on gasoline-range hydrocarbon production by oleic basic soap pyrolysis was carried out. The ratios of calcium to magnesium used were 15%, 35%, 50%, 65%, and 85% with constant Zn. Oleic basic soap was obtained by saponification with the modified fusion method. Pyrolysis experiments were carried out at 450 °C using a semi-continuous reactor with a feed flow rate of 5 g/15 min. The process produced three fractions, i.e., gas, solid, and liquid (bio-hydrocarbon + water). The gas products were characterized by GC-TCD, and the results showed the presence of carbon dioxide, hydrogen, nitrogen, oxygen, and methane. Based on the GC-FID and FT-IR results, the bio-hydrocarbon comprised mainly homologous hydrocarbon from carbon number C7 to C19 containing n-alkanes, alkenes, various iso-alkanes, and some oxygenated compounds. All calcium ratios in the oleic basic soap produced hydrocarbon in the range of gasoline (C7-C11) as the dominant product. The maximum yield of gasoline (74.86%) was achieved at 15% calcium.